PENGARUH BEBAN PAJAK TANGGUHAN, ASET PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Meria Meriana Gulo; Agoestina Mappadang (Universitas Multimedia Nusantara, 2022)
Abstract— The purpose of this study is to understand and analyze the effect of earnings management variables in terms of taxation by using deferred tax expense, deferred tax assets and tax planning on consumer goods manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. 35 companies become research sample through the selection of purposive sampling method as a method of determining the sample with certain provisions and considerations. Panel data regression method with statistical software views is used in this study. The data collection needed is the published annual report of consumer goods manufacturing companies for the period 2016 to 2020. The researcher used the method of quantitative descriptive analysis of logistic regression. From the results of research that has been done, it is found that in terms of taxation, the burden of deferred tax, assets on deferred tax and tax planning is not significant on earnings management actions. Deferred tax assets show negative results, this is because earnings management is carried out to minimize company expenses. Meanwhile, tax planning shows negative results where tax planning is carried out in order to minimize profits to achieve shareholder goals Keywords: Beban Pajak Tangguhan; Aset Pajak Tangguhan; Perencanaan Pajak; Manajemen Laba